2013
DOI: 10.1111/jocn.12264
|View full text |Cite
|
Sign up to set email alerts
|

A Rasch‐based dimension of delivery experience: spontaneous vs. medically assisted conception

Abstract: The delivery perception dimension clearly discriminates between women's types of conception and identifies relevant differences in their birth experience, which are interesting for their clinical implications within a prognostic and intervention perspective of support provision in the early postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…It was developed and evaluated in 1987. Therefore it would be appropriate to perform further testing and updating of its psychometric properties.Women’s delivery experience measures/MFRM [32]Mannarini et al (2013)ItalyTo assess birth experiences after both spontaneous and medically assisted conception.The statistical analysis was made by using the Rash model with the purpose of defining and validating a latent dimension for birth perception [32]. The maternal satisfaction scale for caesarean section/MSS-caesarean section [35]Morgan et al (1999)CanadaTo measure maternal satisfaction in women undergoing elective or non-emergent caesarean section under regional anaesthesia.Developed by anaesthesiologists and two of the dimensions are measuring satisfaction with anaesthetics and side-effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was developed and evaluated in 1987. Therefore it would be appropriate to perform further testing and updating of its psychometric properties.Women’s delivery experience measures/MFRM [32]Mannarini et al (2013)ItalyTo assess birth experiences after both spontaneous and medically assisted conception.The statistical analysis was made by using the Rash model with the purpose of defining and validating a latent dimension for birth perception [32]. The maternal satisfaction scale for caesarean section/MSS-caesarean section [35]Morgan et al (1999)CanadaTo measure maternal satisfaction in women undergoing elective or non-emergent caesarean section under regional anaesthesia.Developed by anaesthesiologists and two of the dimensions are measuring satisfaction with anaesthetics and side-effects.…”
Section: Resultsmentioning
confidence: 99%
“…These included: The Childbirth Trauma Index for adolescents [22] (overall quality mark of 2); The Perception of Birth Scale [23, 24] (overall quality marks of 3); Support and Control in Birth [25] (overall quality marks of 4); The Childbirth Experience Perception Questionnaire [26] and The Birth satisfaction scale and the Birth satisfaction scale - revised [2729] (overall quality marks of 4.5); The Birth Memories and Recall Questionnaire [30], The labour and delivery satisfaction index [31] (an instrument developed and evaluated in 1987, and in need of further testing and updating of its psychometric properties), the Women’s delivery experience measures [32], and the Childbirth schema scale [33] (overall quality marks of 5).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the high levels of Withdrawal that emerged from the results, future investigations should explore the function and the role played by virtual environments and e-communities during pandemic in-depth, taking into account the roles played by the online environments and by the use of social media in terms of both risks and protective functions ( Faccio et al, 2019 ; Gargiulo and Margherita, 2019 ; Margherita and Gargiulo, 2018 ; Procentese et al, 2019 ; Boursier et al, 2020 ). In this sense, future investigations might be also directed to investigate the changes in the dynamics of social and love relationships ( Mannarini et al, 2013 , 2017a ; Balottin et al, 2017 ; Margherita et al, 2018 ) as well as the role of social support ( Ratti et al, 2017 ) post-lockdown and post-pandemic. In conclusion, recognizing the fundamental value of qualitative investigations to shed light on the inner aspects and subjective meanings of personal experiences is also vital ( Margherita et al, 2017 ; Tessitore and Margherita, 2019 ; Tessitore et al, 2019 ; Felaco and Parola, 2020 ; Parola, 2020 ; Parola and Felaco, 2020 ; Tessitore and Margherita, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the LCA assumptions, latent variables are categorical and are structured in a number of classes, which describe the presence or absence of specific peculiarities for each variable. In this study, as regards observed variables, such as roles of the participants, causal beliefs, recommended treatments, social distance, dangerousness and avoidance, a hypothesis was made that a structure of four classes typical of a latent variable X should emerge where each class should identify a profile [51,52] characteristic of a specific role, either professional, or family, or patient, or student, and of the observed variable indicators for schizophrenia. The observed variables were expected to be related in different ways to the participants' roles.…”
Section: Discussionmentioning
confidence: 99%